Kedudukan Sumber Hukum Islam Kedua (Hadis) Dalam Al-Qur'an - Muhammad Lathief Ilhamy Nasution (Al-Kauniyah: Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
Its position as a syara' argument means that in addition to the Qur'an, the sunnah of the Prophet also gives us instructions to know the eternal commandment of Allah which is called syar'i law. The word "sunnah" (????) comes from the word etymologically means: the way that is usually done, whether that way is something good, or bad. Sunnah in terms of ushul scholars is: "whatever is narrated from the Prophet Muhammad SAW., good in the form of words, deeds or confessions and the nature of the Prophet." While the sunnah in terms of fiqh scholars is: "the legal nature of an act that is required to do it in the form of an uncertain demand" with the understanding that the person who does it is rewarded and the person who does not commit it is not guilty. Sunnah according to the understanding of ushul experts as mentioned above is divided into three kinds. First, sunnah qauliyah, namely the words of the Prophet that were heard by his companions and conveyed to others. For example, a friend said that he heard the Prophet say, "Who does not pray because he is asleep or because he forgot, let him do the prayer when he has remembered.” Second, sunnah fi'liyah, namely the act of What was done by the Prophet Muhammad SAW who was seen or known by his companions, then conveyed it to others with his words. For example, a friend said, "I saw the Prophet Muhammad SAW. Perform two rak'ahs of sunnat prayer after the noon prayer." Third, sunnah taqririyah, namely the actions of a friend or his words which were carried out in the presence or knowledge of the Prophet, but were not responded to or prevented by the Prophet. The silence of the Prophet was conveyed by friends who witnessed to others with his words.